2009
DOI: 10.1002/ijc.24610
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and KRAS status of primary sarcomatoid carcinomas of the lung: Implications for anti‐EGFR treatment of a rare lung malignancy

Abstract: Sarcomatoid carcinomas (SC) of the lung are uncommon malignant tumors composed of carcinomatous and sarcomatous cell components and characterized by a more aggressive outcome than other histological subtypes of nonsmall cell lung cancer (NSCLC). Although epidermal growth factor receptor (EGFR)‐targeted therapies have emerged as a promising therapeutic approach in patients with advanced typical NSCLC such as adenocarcinoma, the potential clinical activity of these drugs in lung SC is still unknown. To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 42 publications
(68 reference statements)
4
74
1
1
Order By: Relevance
“…In our patients with pulmonary PC, the male or smoker predominance was similar to previous reports [ [4][5][6]. Only a single study has previously addressed PD-L1 expression in pulmonary SCs, and it demonstrated that PD-L1 was frequently expressed in up to 69.2% of cases [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our patients with pulmonary PC, the male or smoker predominance was similar to previous reports [ [4][5][6]. Only a single study has previously addressed PD-L1 expression in pulmonary SCs, and it demonstrated that PD-L1 was frequently expressed in up to 69.2% of cases [14].…”
Section: Discussionsupporting
confidence: 89%
“…Of these, PCs, accounting for the majority of pulmonary SCs, show highly aggressive biological behaviour and resistance to chemotherapy and radiotherapy [1][2][3][4]. Meanwhile, genetic alterations eligible for molecular targeted therapies are rarely in pulmonary PC [5,6], thus demanding development of a novel therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, both neoadjuvant and adjuvant treatment showed no significant influence on survival or recurrence. Until now, innovative treatments such as monoclonal antibodies that target epidermal growth factor receptor mutations have shown no definitive effect on the outcome [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Molecularly-targeted tumor therapy has previously been studied with findings indicating that certain oncogenes, growth factors and tumor-suppressor genes are associated with adrenocortical carcinoma tumorigenesis. It should be noted that epidermal growth factor receptor (EGFR) is overexpressed in the majority of adrenocortical carcinomas (34), and has been demonstrated to have a significant role in sarcomatoid carcinomas (35,36). Anti-EGFR therapy may comprise a feasible approach for the improvement of prognosis in patients with adrenal sarcomatoid carcinomas.…”
Section: Discussionmentioning
confidence: 99%